2018
DOI: 10.1155/2018/6165493
|View full text |Cite
|
Sign up to set email alerts
|

Through-Focus Vision Performance and Light Disturbances of 3 New Intraocular Lenses for Presbyopia Correction

Abstract: Purpose To compare the through-focus visual performance in a clinical population of pseudophakic patients implanted with two new trifocal intraocular lenses (IOLs) and one extended depth of focus IOL. Methods Prospective, nonrandomized, examiner-masked case series. Twenty-three patients received the FineVision® and seven patients received the PanOptix™ trifocal IOLs. Fifteen patients received the Symfony extended depth of focus IOL. Mean age of patients was 63 ± 8 years. Through-focus visual acuity was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 31 publications
11
100
2
5
Order By: Relevance
“…However, some of the commercially available techniques are limited in their ability to discriminate the light disturbance in all directions or do not measure the detailed shape and irregularity features. Previous studies showed an increase of about 15-23% in light distortion by multifocal intraocular lens (IOL) when compared to monofocal IOL implantation, with trifocal IOL inducing lower values of light distortion than extended depth of focus IOL [26] or bifocal IOLs.15 So far, few studies evaluated the perception of light disturbances in multifocal CL wearers. Besides, the contribution of dominance and the difference in optical design within the same multifocal CL, as well as the binocular summation effect are not completely known [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the commercially available techniques are limited in their ability to discriminate the light disturbance in all directions or do not measure the detailed shape and irregularity features. Previous studies showed an increase of about 15-23% in light distortion by multifocal intraocular lens (IOL) when compared to monofocal IOL implantation, with trifocal IOL inducing lower values of light distortion than extended depth of focus IOL [26] or bifocal IOLs.15 So far, few studies evaluated the perception of light disturbances in multifocal CL wearers. Besides, the contribution of dominance and the difference in optical design within the same multifocal CL, as well as the binocular summation effect are not completely known [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hamid and Sokwala [13] reported in a comparative study that the perception of halos with a trifocal IOL was more disturbing compared to EDOF IOLs. However, other authors such as Escandón-García et al [22] found in a prospective case series that objective dysphotopsia measured with a light distortion analyzer was not reduced in eyes implanted with EDOF IOLs compared to trifocal IOLs. Possibly, in some patients with specific characteristics, the tolerance to the double halo generated by trifocal IOLs [23] is similar to that associated to the halos of lower magnitude generated by EDOF IOLs.…”
Section: Discussionmentioning
confidence: 79%
“…Six studies [18][19][20][22][23][24] better with EDOF IOLs than with monofocal IOLs in the defocus levels from -1.0 to -4.0 D. VA was significantly better in trifocal IOL group than in EDOF IOL group from -2.5 to -4.0 D ( Table 2). The sensitivity analysis showed that no single study significantly changed the pooled estimate, indicating the results of defocus curves were stable.…”
Section: Defocus Curvesmentioning
confidence: 99%
“…Seven studies [10,18,[20][21][22][23][24] reported contrast sensitivity and the results are summarized in Table 3.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation